2016
DOI: 10.25518/1780-4507.13047
|View full text |Cite
|
Sign up to set email alerts
|

Influence de l’enherbement viticole sur les Carabidae (Coleoptera) et intérêt potentiel pour le contrôle de certains ravageurs de la vigne

Abstract: Description du sujet. Cet article traite des populations de carabes observés en vignobles. Objectifs. Les objectifs sont d’évaluer l’impact de différents modes de gestion de l’enherbement viticole sur les populations de carabes et leur potentiel en tant que prédateurs de certains ravageurs de la vigne. Méthodes. Deux vignobles, caractérisés chacun par différentes gestions de l’enherbement, situés dans le canton de Genève (Suisse), ont été échantillonnés à l’aide de 60 pièges à fosse pour différentes gestions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Based on the characteristics of our study fields and the literature, we identified environmental variables related to human presence, seasonal variation and type of habitat. We argue that these variables likely have an effect on bird communities (Guyot et al, 2017; Hanane et al, 2019; Petremand et al, 2016; Pithon et al, 2016).…”
Section: Methodsmentioning
confidence: 94%
“…Based on the characteristics of our study fields and the literature, we identified environmental variables related to human presence, seasonal variation and type of habitat. We argue that these variables likely have an effect on bird communities (Guyot et al, 2017; Hanane et al, 2019; Petremand et al, 2016; Pithon et al, 2016).…”
Section: Methodsmentioning
confidence: 94%